Risk Factors for Malignancy of Branch-Duct Intraductal Papillary Mucinous Neoplasms: A Critical Evaluation of the Fukuoka Guidelines With a Systematic Review and Meta-analysis. Issue 9 (October 2016) - Ricci, Claudio; Casadei, Riccardo; Taffurelli, Giovanni; Zani, Elia; Pagano, Nico; Pacilio, Carlo Alberto; Ingaldi, Carlo; Bogoni, Selene; Santini, Donatella; Migliori, Marina; Di Marco, Mariacristina; Serra, Carla; et al.
Abstract : Objectives: This study aimed to evaluate the accuracy of the risk factors proposed by Fukuoka guidelines in detecting malignancy of branch-duct intraductal papillary mucinous neoplasms. Method: Diagnostic meta-analysis of cohort studies. A systematic literature search was conducted using MEDLINE, the Cochrane Library, Scopus, and the ISI-Web of Science databases to identify all studies published up to 2014. Results: Twenty-five studies (2025 patients) were suitable for the meta-analysis. The "high risk stigmata" showed the highest pooled diagnostic odds ratio (jaundice, 6.3; positive citology, 5.5; mural nodules, 4.8) together with 2 "worrisome features" (thickened/enhancing walls, 4.2; duct dilatation, 4.0) and 1 "other parameters" (carbohydrate antigen 19-9 serum levels, 4.6). Conclusions: An "ideal risk factor" capable of recognizing all malignant branch-duct intraductal papillary mucinous neoplasms was not identified and some "dismal areas" remain. However, "high risk stigmata" were strongly related to malignancy, mainly enhancing mural nodules. Among the "worrisome features, " duct dilatation and thickened/enhancing walls were underestimated, and their diagnostic performance was similar to those of "high risk stigmata." The carbohydrate antigen 19-9 serum level should be added to the Fukuoka algorithm because this value could help in carrying out correct management. Abstract : Supplemental digital content is available in the text.